2012
DOI: 10.1097/ccm.0b013e31823779ca
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulins prevent the breakdown of the blood-brain barrier in experimentally induced sepsis

Abstract: Our study suggests that immunoglobulin G and immunoglobulins enriched with immunoglobulin A and immunoglobulin M improve the integrity of the blood-brain barrier and inhibits cecal ligation and perforation-induced symptoms of sickness behavior in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
34
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 26 publications
3
34
0
Order By: Relevance
“…Previous work suggested that hIgG could saturate the recycling receptor FcRn on endothelial cells and decrease the half-life of pathogenic antibodies in blood (Li et al, 2005). A previous study demonstrated that hIgG reduced blood-brain barrier disruption in a cecal puncture model of sepsis (Esen et al, 2012), though it is difficult to establish whether this was a direct effect or a secondary effect due to a global antiinflammatory response. Here, we found comparable albumin extravasation, a measure of blood-brain barrier integrity, in control and hIgG-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work suggested that hIgG could saturate the recycling receptor FcRn on endothelial cells and decrease the half-life of pathogenic antibodies in blood (Li et al, 2005). A previous study demonstrated that hIgG reduced blood-brain barrier disruption in a cecal puncture model of sepsis (Esen et al, 2012), though it is difficult to establish whether this was a direct effect or a secondary effect due to a global antiinflammatory response. Here, we found comparable albumin extravasation, a measure of blood-brain barrier integrity, in control and hIgG-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…IVIg could, therefore, prevent the loss of tight junction integrity in the brain and consequently protect the BBB whose breakdown contributes to a large part of stroke-induced injury. A recent study investigating the effect of IVIg on BBB integrity in a sepsis model suggested that immunoglobulin G, A, or M improved the integrity of the BBB and inhibited symptoms of sickness in rats [14]. We previously reported that IVIg crosses the BBB and exerts protective effects in a mouse model of stroke [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, regulation of caveolae formation and paracellular junction to prevent microvascular hyperpermeability has become a potential new strategy for septicemia therapy. However, few clinical drugs are available that direct at hyperpermeability in endotoxemia therapy, although preclinical experiments for some new agents have been undertaken to test their roles in endothelial barrier protection (7,25).…”
mentioning
confidence: 99%